(untitled) (Journal of Innovation in Academia, 2025)
This paper examines the perceived impact of microfinance on livelihood improvement in Kaski district of Nepal. The study is based on a primary survey limited to five MFIs working in rural parts of Kaski district. The impact of microfinance services on people’s livelihoods was examined using a descriptive and explanatory research. The livelihood status of the clients has been measured in terms of economic (microbusiness creation, income level, saving habits, productive investment, consumption, and capital expenditures) and social condition (educational status, health status, women empowerment, and social networking) of the clients after microfinance intervention. The researcher randomly selected 150 clients involved in microfinance institutions for the last three or more years. The study finds a significant impact of microfinance on the livelihood improvement of poor and marginalized people. Microfinance interventions have significantly improved clients’ economic condition, including microbusiness creation, income level, saving habits, productive investment, consumption, and capital expenditures.